(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Aims: To compare safety and efficacy of diazepam and clobazam. Objectives: This study was undertaken to compare the effectiveness of intermittent clobazam versus diazepam therapy in preventing the recurrence of febrile convulsion and assess adverse effects of each drug. Methods: This is a hospital based randomized controlled trial was performed on neurologically normal children with the history of simple febrile convulsion and normal electroencephalogram without any evidence of acute central nervous system infection, done in Chattagram Maa Shishu-O-General Hospital/CMSOGH between November12 to April13. A total of 37 patients were randomly prescribed with oral clobazam and diazepam was given in 35 patients when they developed a febrile disease. All the patients were monitored regarding developing seizure and adverse effects of the drugs. All patients were followed for 12 months. Results: It was observed that 243 attacks of fever occurred during the period, including 116 attacks in the clobazam group and 127 episodes in the diazepam group. Recurrence of convulsion occurred in 2 (1.7%) subjects in the clobazam group, and in 4(3.1%) cases in the diazepam group. Twenty cases (54%) in the diazepam group and 5 (14.2% ) cases in the clobazam group developed drowsiness and sedation during the follow-up period. Conclusion: Intermittent clobazam therapy has better advantage over diazepam with similar efficacy but significantly lower adverse effects such as drowsiness and sedation. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21027